CCL13 and human diseases - Li, Laifu; Dai, Fei; Wang, Lianli; Sun, Yating; Mei, Lin; Ran, Yan; Ye, Fangchen (Frontiers in Immunology, 2023)
CCL13/MCP-4 belongs to the CC chemokine family, which induces chemotaxis in many immune cells. Despite extensive investigations into its role in various disorders, a comprehensive review of CCL13 is currently unavailable. In this review, we summarize the involvement of CCL13 in human disorders and the CCL13-centered treatments that have been developed. The role of CCL13 in rheumatic diseases, skin diseases, and cancer is relatively well-established, with some reports indicating its involvement in ocular disorders, orthopedic diseases, nasal polyps, and obesity. We also provide an overview of studies that reported minimal CCL13-related findings in HIV, nephritis, and multiple sclerosis. Although CCL13-mediated inflammation is often implicated in disease pathogenesis, interestingly, it may play a protective role in certain diseases such as primary biliary cholangitis (PBC) and suicide.